Information security management of strategically important enterprises in the conditions of challenges and threats (Economics and region, 2022)
The article substantiates the importance of managing information security of enterprises of strategic importance for the economy and security of the state. Considering the current realities of the war, the national economy is experiencing a large-scale shock, and therefore it is necessary to apply a set of information, organizational, economic and legal measures to restore entire industries. The authors substantiates the need to regulate and institutionally define the list of strategic industries, on the stable and secure functioning of which the recovery of the real sector of Ukraine's economy in the post-war period will depend. In terms of realization of national interests, along with the development of strategic industries, it is advisable to take into account the functioning of strategically important enterprises that organically complement and detail them. Given the impact of strategically important enterprises on the economic and national security of the country as a whole, the author proposes to define the status of strategically important enterprises and to legislate for the possibility of state control over the activities of business entities of strategic importance to the state. The research proves the role of security-oriented activities of strategically important enterprises during the wartime period and post-war reconstruction of Ukraine. The authors focus on the fact that in the context of digitalization, which has led to the emergence of new risks and threats to the functioning of national economies and revealed critical problems in the information sphere, ensuring information security is a prerequisite for the stable functioning of strategically important enterprises. The application of an institutional approach to the management of information security of strategically important enterprises is proposed. It is proved that building a reliable information security system should be based on timely identification of threats to information security. The systematization of threats to information security of strategically important enterprises, taking into account the provisions of current legislation, is rightly determined as the basis for their prevention and the basis for making effective management decisions to ensure the functioning of strategically important enterprises on the basis of information security.
Keywords: information security; strategically important enterprises; security-oriented activities; threats